Bioengineering approach for the design of magnetic bacterial cellulose membranes - Sundaravadanam Vishnu Vadanan; Rupali Reddy Pasula; Neel Joshi; Sierin Lim (Communications Materials)
Abstract Biopolymer research has led to the development of novel products through innovative strategies. Their functionalization is typically achieved by physical/chemical methods that require harsh chemicals or mechanical treatments. These functionalities could be alternatively achieved by employing bioengineering design methods. We demonstrate, a bioengineered dual-microbial approach to create functional bacterial cellulose from microbial workhorses. Komagataeibacter hansenii ATCC 53582 is used to produce bacterial cellulose and engineered E. coli is used to functionalize the matrix with a recombinant fibrous protein. The E. coli harbours synthetic genes for the secretion of amyloid curli protein subunit (CsgA) tagged with short functional M6A peptide domains. The incorporation of M6A-functionalized amyloid proteins into bacterial cellulose facilitates magnetite nanoparticle nucleation. We achieved a saturation magnetization of 40 emu g−1, a three-fold increase compared to existing strategies. The magnetic bacterial cellulose films demonstrate cytocompatibility and accelerate cell migration in the presence of magnetic field.